Efficient avalanche photodiodes with a WSe₂/MoS₂ heterostructure via two-photon absorption - Son, Bongkwon (2023)
Two-dimensional (2D) materials-based photodetectors in the infrared range hold the key to enabling a wide range of optoelectronics applications including infrared imaging and optical communications. While there exist 2D materials with a narrow bandgap sensitive to infrared photons, a two-photon absorption (TPA) process can also enable infrared photodetection in well-established 2D materials with large bandgaps such as WSe2 and MoS2. However, most of the TPA photodetectors suffer from low responsivity, preventing this method from being widely adopted for infrared photodetection. Herein, we experimentally demonstrate 2D materials-based TPA avalanche photodiodes achieving an ultrahigh responsivity. The WSe2/MoS2 heterostructure absorbs infrared photons with an energy smaller than the material bandgaps via a low-efficiency TPA process. The significant avalanche effect with a gain of ∼1300 improves the responsivity, resulting in the record-high responsivity of 88 μA/W. We believe that this work paves the way toward building practical and high-efficiency 2D materials-based infrared photodetectors.